Acute airway management - Panda, Nikhil (Ann Cardiothorac Surg, 2018)
Acute airway management has challenged clinicians for nearly four millennia. History underscores the discoveries of surgeons and anesthesiologists, whose advances in technology and surgical technique have transformed management algorithms from primarily surgical tracheostomy, to transoral endotracheal intubation under direct laryngoscopy. Despite this progress and a better understanding of airway anatomy, physiology and pathogenesis of disease, the acute airway, whether obstructed, traumatically disrupted, or externally compressed, remains a life-threatening challenge. The role of all clinicians in acute airway management is patient stability and emergent control of the airway to ensure patency as well as adequate oxygenation and ventilation. The standard of care remains transoral intubation under direct laryngoscopy with use of indirect laryngoscopy as a first adjunct. If unsuccessful, surgical intubation of the trachea via cricothyroidotomy with subsequent conversion to open tracheostomy is the procedure of choice. While there is growing support for the use of percutaneous tracheostomy as an alternative to surgical intubation of the trachea after failed transoral intubation, the potential for damage to critical neck structures and longer time-to-intubation must be considered. In this perspective, we provide a history of acute airway management, highlighting milestones in the fields of airway surgery and anesthesia. We present a review of current medical and surgical approaches to managing the acute airway, including the risks, benefits and appropriateness of each approach with respect to patient stability, available equipment, clinician training and patient outcomes. We conclude with an emphasis on the role of the thoracic surgeon in prevention and the critical nature of regular surveillance of patients with chronic, partial tracheal obstruction.